Influence of the Assembly Method of Sleeve Joints on Their Strength - Rudawska, Anna; Miturska, Izabela; Wahab, Magd Abdel; Stančeková, Dana; Ťavodová, Miroslava (Manufacturing Technology Journal, 2020)
The aim of the study was to compare the strength of assembly joints of sleeve elements made of different structural, polymeric materials. Experimental tests were carried out to determine the mechanical properties of adhesive and welded joints. Adhesive joints were made of polyvinyl chloride pipes with the use of three types of adhesives: Epidian 53/PAC/100:80, Epidian 53/TFF/100:22, Vodaro 15010-VO. The welded joints were made of polypropylene pipes. All of the joints have been made with the use of a pipe fitting allowing for correct joints. Then the completed joints were subjected to destructive strength tests. The obtained results made it possible to carry out statistical analysis, which aimed at determining significant differences between the various methods of assembly. The tests carried out proved that the adhesive joints made with the Vodaro 15010-VO one-component adhesive were characterized by the highest strength - 2.30 MPa. The lowest strength was obtained in the case of adhesive joints made with Epidian 53/TFF/100:22 - 0.45 MPa epoxy ad-hesive composition. Statistical analysis showed that the strength obtained in case of adhesive joints made with epoxy compositions differs significantly from the strength of adhesive joints made with Vodaro adhe-sive. No significant differences at the assumed level of significance α=0.05 were also observed in the case of the strength of PP-R adhesive joints made with Vodaro adhesive and the strength of PVC-U welded joints.
Keywords: Adhesive joints; welded joints; sleeve joints